Активность молодой звезды EPIC 204376071 из ассоциации Upper Sco - Саванов, И. С. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
По наблюдениям миссии К2 космического телескопа Кеплер выполнено исследование активности EPIC 204376071-молодого объекта, члена ассоциации Upper Sco с возрастом 11±3 млн лет, кривая блеска которого обладает единичным затмением суточной продолжительности с глубиной около 80%. EPIC 204376071 является маломассивным М-карликом с массой 0.16 M . По наблюдениям кампании С15 миссии К2 мы уточнили период вращения и амплитуду переменности блеска звезды, а также по стандартной методике оценили величину параметра запятненности A в абсолютной мере. Величина периода вращения звезды Р равна 1.6270 ±0.030 сут. Площадь пятен на поверхности EPIC 204376071 превосходит максимальную площадь пятен на Солнце и составляет величину порядка 7900 м.д.п. Представлены результаты восстановления температурных неоднородностей на поверхности EPIC 204376071. На построенной карте хорошо различимы две холодные области, разделенные по долготе примерно на 150o. Для оценки свойств вспышечной активности EPIC 204376071 была рассмотрена одна наиболее достоверная вспышка с амплитудой блеска около 4%. Using the observations of the K2 mission of the Kepler Space Telescope we studied the activity of EPIC 204376071 - a young object in the Upper Sco association with the age of 11 ± 3 million years, whose light curve has a single occultation of daily duration with a depth of about 80%. EPIC 204376071 is a M-dwarf of mass 0.16  M . On the base on the observations of the C15 campaign of the K2 mission we estimated the rotation period, amplitude of the variability of the brightness of the star and the spottedness parameter A in absolute measure using the standard method. The magnitude of the rotation period of the star P is 1.6270 ± 0.030 days. The area of spots on the surface of EPIC 204376071 exceeds the maximum area of spots on the Sun and is about 7900 MSH. The results of the restoration of temperature inhomogeneities on the surface of EPIC 204376071 are presented. Two cool regions separated in longitude by about 150o are clearly distinguishable on the constructed map. Characteristics stellar flare activity are estimated on the base of one of the most reliable flare. The flare amplitude is about 4%. The measured relative energy RE of the flare was 212 sec. The calculated energy of the flare Efl equal to 1.1·1034 erg (logEfl = 34.05). The corresponding probable value of the coronal mass ejection can reach 4.1·1020 g. Possible explanations of a single occultation of 1-day duration with a depth of about 80% on the EPIC 204376071 light curve are discussed.
Keywords: Астрофизика